THE SIDE JOB PHENOMENON AS AN EFFORT TO FULFILL FAMILY NEEDS - Mahbubah, Zaematul; Wijaya, Atika (Program Studi Sosiologi Universitas Malikussaleh, 2024)
This research aims to determine the factors behind the craftsmen community in Pucang village making souvenir crafts as a side job to fulfill family needs. The research uses primary data and secondary data. Primary data was obtained from fifteen informants, by means of direct interviews and observation. Secondary data was obtained from the internet via publish perish, Google Scholar to obtain articles and theses related to research. The method used is qualitative with an approach using Colmen's rational choice theory. The research results show that the factors behind the existence of side jobs are the craftsman's hereditary factors, free time, and not much capital. And the implementation of a side job as a craftsman is a system of dividing work time between working in the fields and working as a craftsman. So that with this side job, people have a steady income and can meet their family's living needs.